Variability of the Composition of Growth Factors and Cytokines in Platelet-Rich Plasma From the Knee With Osteoarthritis - Ha, Chul-Won; Park, Yong-Beom; Jang, Jae Won; Kim, Manyoung; Kim, Jin-A; Park, Yong-Geun (Arthroscopy, 2019)
To investigate the composition and concentration of growth factors and cytokines in platelet-rich plasma (PRP) with knee osteoarthritis and to explore the association of the concentration of growth factors and cytokines with the platelet count of PRPs. Patients who visited outpatient clinic with symptomatic knee osteoarthritis (Kellgren-Lawrence grades 1 to 3) and had no blood dyscrasia were enrolled from October 2014 to March 2015. PRPs were obtained using a commercial system. Concentrations of growth factors and cytokines were measured with an enzyme-linked immunosorbent assay. Anabolic factors (platelet-derived growth factor [PDGF]-AA, -BB, and -AB, transforming growth factor-β, vascular endothelial growth factor [VEGF], epidermal growth factor [EGF], basic fibroblast growth factor [bFGF], and insulin-like growth factor 1), catabolic factors (interleukin [IL]-1β and matrix metalloproteinase 13), and catabolic blockers (IL-1 receptor antagonist) were included. The degree of variation was determined by coefficient of variation (CoV). 105 patients were included. Growth factors and cytokines showed wide variation. bFGF showed the highest variation (CoV 78.45), and transforming growth factor-β1 showed the lowest variation (CoV 5.30). Platelet count in PRP showed a positive correlation with PDGF-BB and -AB, and VEGF (r = 0.270, P = .005; r = 0.231, P = .018; and r = 0.200, P = .041, respectively) and was negatively correlated with IL-1β (r = -0.220, P = .025). Growth factors and cytokines in PRPs obtained from patients with knee osteoarthritis show a wide variation; the highest variation was shown in bFGF. Platelet counts associated positively with PDGF-AB and -BB and VEGF and negatively with IL-1β. This information leads to the concept that variation and association of specific factors needs to be taken into consideration for future investigations of PRPs in clinical application in patients with knee osteoarthritis.